Perception of Undergraduate Pharmacy Students of Case-Based Learning as a Tool in Teaching Pharmacy Management Course - AlRasheed, Hayam Ali (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background: Case-Based Learning (CBL) has become a significant pedagogical approach in higher learning institutions, especially in disciplines that involve problem-solving and critical thinking. This research aims at identifying the perception that undergraduate pharmacy students have toward CBL in a pharmacy management course. Materials and Methods: In this descriptive research study, 69 fourth-year pharmacy students from a university in Saudi Arabia were chosen. The data was collected through a self-administered standardized questionnaire and the participants’ demographic information, CBL perceptions and feedback were analysed. Results: The results indicated that 63.77% of students agreed that CBL helped instructors deliver material adequately. It was also observed that 77% of the students agreed that CBL enhanced materials’ delivery; 55.7% said it enlightened them more; and 44.92% agreed it helped in preparation and reading beforehand. Thus, 92% of the respondents agreed that it enhanced preparation. All the parameters of active participation, engagement and interaction increased for most of the students; however, it was observed that there were some discrepancies in the level of understanding and interaction. Conclusion: The study reveals the possibility of adopting CBL in a pharmacy curriculum, though with recommendations for improvement to address variety in students’ learning styles. Possible future strategies include educating the instructors and reducing the level of the case study’s complexity to allow more students’ participation and satisfaction.
Keywords: Case-Based Learning (CBL); Pharmacy Management Education; Undergraduate; Pharmacy Students; Active Learning Strategies; Pedagogical Approaches in Pharmacy